Sistem Informasi Geografis Pemetaan Kawasan Pembibitan Buah - Muhammad Rafly; R Arri Widyanto; Setiya Nugroho (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Sriwedari Village, Salaman District, is one of the villages in the Salaman region which is known as a fruit nursery center. Favorite fruit seeds in this area, including durian, avocado and longan fruit seeds. The diversity of types of fruit seeds, often causes problems for farmers who need fruit seeds as desired, because the information needed is not yet available, to overcome this it is necessary to build a geographic information system for mapping fruit nursery areas that are used to make it easier for users to find the fruit seeds needed. The method used in developing this system is prototyping, using the Model-View-Controller (MVC) framework. The results of this study are in the form of a geographic information system used by fruit nursery entrepreneurs to inform their whereabouts on the map and the types of seeds they provide. This Geographic Information System makes it easy for users to find the desired fruit seeds by displaying several entrepreneurs who have the seeds the user wants. Based on the results of the tests that have been carried out, the user perception is Strongly Agree of 0.73% which indicates the system is easy to use and easy to understand. Black box testing also shows that this system is successful. This research is expected to help users find information about fruit seedlings in the village of Sriwedari Salaman.